Spontaneous coronary artery thrombosis in the setting of active lupus mesenteric vasculitis. (July 2015) - Reddy, Yogesh N V; Sundaram, V; Tam, M; Parikh, S A
A 33-year-old male with systemic lupus erythematosus (SLE) presented with acute abdominal pain and was found to have lupus mesenteric vasculitis on imaging and during exploratory laparotomy. Post laparotomy he continued to have persistent nausea and dyspepsia and an electrocardiogram showed evidence of an inferior ST elevation myocardial infarction (STEMI). Emergency cardiac catheterization showed evidence of thrombotic right coronary artery occlusion. His coronaries were otherwise normal with no evidence of underlying coronary artery disease. Extensive workup with trans-esophageal echo, serologies for antiphospholipid antibody syndrome (APS) and bubble study was negative. This effectively ruled out Libman–Sacks endocarditis, APS-induced arterial thrombus and paradoxical emboli as potential causes of his STEMI. By exclusion of other causes, the etiology of his STEMI was felt to be secondary to in-situ coronary artery thrombosis in the setting of active SLE. To the best of our knowledge, this is the first report of a patient with SLE presenting with both lupus mesenteric vasculitis and in-situ coronary arterial thrombosis in the absence of APS.